A Study in the Importance of the Branch of Economic Engineering in the Labour Marcet - (Fortuzi), Stela Jorgji (European Journal of Economics and Business Studies, 2023)
This research has as its main objective to analyze the characteristics, size of the market and other indicators for graduate students in Economic Engineering. They should familiarize with the business sectors they will be working after graduating or in the future. To further know about the opportunities, the university offer for employment of graduate students and also analyze the importance of practices for facilitating the process of integration in the labor market. Significance of this topic is “huge” for the students that are enrolled in the Economic Engineering program, freshly graduates or other potential students. This study program is relatively new compared to other engineering programs and employers are not completely informed about the position of an economic engineer in the labor market. This leads to the underestimation of these engineers. Students who pursued a degree in Economic Engineering have limited information about the labor market they could operate and work on. It is vital for the students to get to know better of what the market demands are, opportunities and difficulties they might face. One of the most important aspects of this topic is the help that university must offer to its students to better understand about their future job position as an economic engineer. Universities that offer this degree program must integrate their mandatory policies to make a smooth process for the graduates. Students should be fully informed about the required skills of economic engineer labor market.
Keywords: Academic institutions, Economic Engineering, Graduate students